Rhesus Brain Transcriptomic Landscape in an ex vivo Model of the Interaction of Live Borrelia Burgdorferi With Frontal Cortex Tissue Explants - Ding, Zhe; Ma, Mingbiao; Tao, Lvyan; Peng, Yun; Han, Yuanyuan; Sun, Luyun; Dai, Xiting; Ji, Zhenhua; Bai, Ruolan; Jian, Miaomiao; Chen, Taigui; Luo, Lisha; et al. (Frontiers in Neuroscience, 2019)
Lyme neuroborreliosis (LNB) is the most dangerous manifestation of Lyme disease caused by the spirochete Borrelia burgdorferi which can reach the central nervous system most commonly presenting with lymphocytic meningitis; however, the molecular basis for neuroborreliosis is still poorly understood. We incubated explants from the frontal cortex of three rhesus brains with medium alone or medium with added live Borrelia burgdorferi for 6, 12, and 24 h and isolated RNA from each group was used for RNA sequencing with further bioinformatic analysis. Transcriptomic differences between the ex vivo model of live Borrelia burgdorferi with rhesus frontal cortex tissue explants and the controls during the progression of the infection were identified. A total of 2249, 1064, and 420 genes were significantly altered, of which 80.7, 52.9, and 19.8% were upregulated and 19.3, 47.1, 80.2% were downregulated at 6, 12, and 24 h, respectively. Gene ontology and KEGG pathway analyses revealed various pathways related to immune and inflammatory responses during the spirochete infection were enriched which is suggested to have a causal role in the pathogenesis of neurological Lyme disease. Moreover, we propose that the overexpressed FOLR2 which was demonstrated by the real-time PCR and western blotting could play a key role in neuroinflammation of the neuroborreliosis based on PPI analysis for the first time. To our knowledge, this is the first study to provide comprehensive information regarding the transcriptomic signatures that occur in the frontal cortex of the brain upon exposure to Borrelia burgdorferi, and suggest that FOLR2 is a promising target that is associated with neuroinflammation and may represent a new diagnostic or therapeutic marker in LNB.